Experimental and investigation on parallel operation of three phase transformer for star to star and delta to star connections / Mohd Nazrye Md. Desa - Md. Desa, Mohd Nazrye (1997)
This paper discusses the experimental and investigations on parallel operation of three phase transformers for star to star and delta to star connections. The study is based on the open circuit and short circuit test of a three phase transformer testing unit rated for 2kVA, 240V and 50Hz. Almost all major power generation and distribution system are AC three-phase. Most electrical energy is generated and transmitted using a three phase system. Thus three phase transformers play major role in power industry. There are four common combinations of connections. The connections involved are star-star, star-delta, delta-star and delta-delta. The study is basically on star-star and delta-star connection.